15 kV class high-voltage electrical vacuum feedthrough. (September 2018) - Pan, Wanjiang; Zhu, Yinfeng; Hu, Nannan; Wu, Cheng; Wang, Ke; Cao, Yi; Chen, Huang
Highlights: The developed 15 kV class high-voltage electrical vacuum feedthrough can fulfil the working requirements even if it is under Paschen discharge condition. The developed 15 kV class high-voltage electrical vacuum feedthrough is helium tight and insulating to high-voltage. The developed 15 kV class high-voltage electrical vacuum feedthrough is resistant against thermal shrinking. Abstract: In the feeder system of the Experimental Advanced Superconducting Tokamak (EAST), the high-voltage (HV) electrical vacuum feedthrough plays an important role in transmitting the voltage signals from one vacuum environment to anther vacuum environment under cryogenic temperature. Due to no commercial solutions, the feedthroughs for EAST were developed in the Institute of Plasma Physics, Chinese Academy of Sciences. In this paper, the structural design, electrical analysis, structural analysis and experiments involving thermal cycle, helium gas tightness, HV-leakage current and Paschen discharge are presented. The experimental result indicates that the leak rate of the developed feedthroughs was less than 1 × 10 −9 Pa·m 3 ·s −1 . After the 5 thermal cycles from room temperature (RT) to 77 K, the HV-leakage current experiment under 10 −3 Pa vacuum environment and the Paschen discharge experiments of feedthroughs were performed, the leakage current under 15 kV DC is lower than the allowable value 5 µA, and the leakage currents in helium gas and nitrogen gas from 1 Pa to 50 kPa are lower than the allowable value 10 µA.